Student Perceptions of the Visual Design of Learning Management Systems - Stoesz, Brenda M.; Niknam, Mehdi (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
Research on the impact of the visual design of the user interface of learning management systems (LMS) on learning experience is sparse. The purpose of this study was to conduct a preliminary examination of students’ perceptions of the visual design of their postsecondary institutions’ LMS and their learning experiences using survey methodology (N= 46). Students generally agreed that the course homepages were well organized and that the LMS colours, while deemed moderately to very important, did not enhance learning or increase the ability to remember course content. However, more positive perceptions of the visual appearance of the LMS were associated with greater satisfaction with grades. Expected end of term grade point average was negatively correlated with the degree to which students perceived that colour enhanced their learning. Students reported a greater satisfaction with the contribution of the LMS to learning correlated to the number of school terms they had used an LMS, their LMS proficiency, and their perceptions about the visual appeal of the LMS design. Together, these results suggest that exploring the impact of LMS colour and other dimensions of visual design on student engagement and learning are important and have practical value for LMS developers, instructional designers, and instructors.